2010
DOI: 10.1007/s13197-010-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of mango and potential of non-destructive techniques for their measurement — a review

Abstract: The king of fruits "Mango" (Mangifera indica L.) is very nutritious and rich in carotenes. India produces about 50% of the total world's mango. Many researchers have reported the maturity indices and quality parameters for determination of harvesting time and eating quality. The methods currently used for determination of quality of mango are mostly based on the biochemical analysis, which leads to destruction of the fruits. Numerous works are being carried out to explore some non-destructive methods such as N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 128 publications
4
51
0
4
Order By: Relevance
“…At mature (unripe) stage, the TA content was 1.06% while it reduced to about one third at ripen stage. These results agreed with that reported by Jha et al [17] which suggested that acidity of mango-flesh decreased significantly during ripening. …”
Section: Tss and Tasupporting
confidence: 93%
See 1 more Smart Citation
“…At mature (unripe) stage, the TA content was 1.06% while it reduced to about one third at ripen stage. These results agreed with that reported by Jha et al [17] which suggested that acidity of mango-flesh decreased significantly during ripening. …”
Section: Tss and Tasupporting
confidence: 93%
“…This might be due to hydrolysis of polysaccharide. These results were consistent with the reported value [17]. It is also reported that starch is the main carbohydrate present in mature green pulp, which is being hydrolyzed by some enzymes such as -and -amylases [18].…”
Section: Starch Contentsupporting
confidence: 93%
“…The district Shikarpur is situated in the northern part of Sindh Pakistan [7][8][9]. The summers are very hot and the winters are mild to cold.…”
Section: Methodsmentioning
confidence: 99%
“…Mangotraded market is growing rapidly, as the demand for traditional varieties in western markets is increasing. There is a huge variety of mango cultivars and their potential should be studied (JHA et al, 2010). Thus, introducing these crops in new producing regions become promising, especially areas that present edaphoclimatic relevant characteristics to the development thereof.…”
Section: Introductionmentioning
confidence: 99%